Building the foundation text for Nanyang Technological University : multilingual corpus (NTU-MC) - Tan, Li Ling. (2012)
The NTU-MC is a multilingual corpus that taps on the availability of multilingual text available in Singapore. The current version of NTU-MC contains a total of ~375,000 words (15,096 sentences) for the NTU-MC in 6 languages (English, Chinese, Japanese, Korean, Indonesian and Vietnamese) from 6 language families (Indo-European, Japonic, Austro-Asiatic, Sino-Tibetan, Austronesian and Korean as a language isolate); all text in English, Chinese, Japanese, Korean and Vietnamese were Part Of Speech (POS) tagged. This project focuses on compiling the foundation text for the NTU-MC and this dissertation describes the motivations, the corpus compilation process and internal and cross-corpora evaluation of the corpus output. The corpus will be made available to the public under the Creative Common – Attribute 3.0 Unported license in Summer 2011.